Waste management of Sugar Central in Western Visayas - Canete, ray Omega; Faeldonia, Francis Rean.; Fontanilla, Meniveh; Mamerto, Marissa; Mesa, Mary Mae. (1997)
Sugar Milling Industry is one of the oldest industry in the Philippines. It was considered to be one of the export commodities of the country not until the sugar crisis in the 1970s and the current shift in the sugar policies. Like any other industries, sugar centrals emit waste materials that could be harmful to the environment. This study describes the typical streams, wastes management practices, and pollution barriers, and efficiency of typical sugar milling facility. Furthermore, the study also consists of a careful review of the waste management system with regard to the environment. The study revealed that Sugar Centrals in Western Visayas are not socially responsible. The presence of waste disposal systems exists only in order to comply with the laws and regulations set by the government. On the part of the government, there is a need in refocusing its existing policies regarding the pollution and waste standards.
Business Research Paper (BA 200 - Business research). -- [Iloilo City] : UPV-[CM], March 1997.